Communicative Voice and Articulation - McCabe, Bernard P. (Holbrook Press, 1970)
Keywords: Voice culture; dept.cmd; faculty_collection

Effects of interrupted normal speech flow on post-interruption speech rates - Sansone, F.E. (IRCS Medical Science: Nervous System, 1978)
Keywords: central nervous system; dept.cmd; human cell; larynx; normal human; speech; ⛔ No DOI found

The effects of microphone spacing on auditory localization - Maxon, A.B.; Mazor, M. (International Journal of Audiology, 1977)
The localization ability of 10 normally hearing adults was determined under varying microphone separations and varying sound source azimuths. The stimuli (white noise bursts) were prerecorded, after being transduced through 'body' hearing aids and then played to the subjects over headphones. Results indicated that there was an improvement in localization ability for all azimuth conditions when the microphones were spaced wider than 12.7 cm apart (15.2-30.5 cm). The smaller the separations (5.5-12.7 cm), the poorer the localization. Localization was always poorer at 30° azimuth (the smallest used) than at any of the other azimuths (0° 30° 60° 90° right and left), regardless of microphone spacing. Implications are made about the relation of these findings to the use of binaural body aids on infants and young children. © 1977 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.
Keywords: Acoustic Stimulation; Audiometry; Auditory Perception; Auditory localization; Binaural amplification; Female; Hearing Aids; Human; Male; Noise; Pediatric amplification; audiology; binaural hearing; child; dept.cmd; directional hearing; methodology; microphone

The initial psychotherapy interview: a content analysis of the verbal responses of novice and experienced therapists. - Cicchetti, Domenic V; Ornston, Patricia S (The Journal of Psychology, 1976)
This study tested and confirmed the clinical impressions that (a) the novice psychotherapist may focus so much upon the exact words and nonverbal behavior patterns of his client (the process of making “concrete” statements) that he may lose sight of the larger picture that his client may be revealing at any given moment during the interview; (b) the experienced psychotherapist, on the other hand, seems to be responding to the words of the patient at a level of abstraction that attempts to integrate and understand the messages that the patient is trying to convey about himself; and (c) this latter process is reflected in the making of relatively more “abstract” comments than is true of the novice. S s were 24 first-year psychiatric residents and 19 staff psychologists and psychiatrists at a veterans hospital and a medical school. The learning theory implications of these findings is discussed. © 1976 Taylor & Francis Group, LLC.
Keywords: Analysis of Variance; Clinical Competence; Comparative Study; Human; Interview, Psychological; Psychotherapy; Verbal Behavior; analysis of variance; article; comparative study; competence; dept.cmd; human; manpower; methodology; psychologic test; psychotherapy; verbal behavior